Effect of preprandial exercise on basal and postprandial intermediary metabolism on people with type 2 diabetes at high altitudes - Garmendia Lorena, Fausto (2019)
Introduction. The population living on high altitudes areas has a different intermediate metabolism than people who is living on coastal areas, characterized by lower glycemia levels. In patients with type 2 diabetes, who reside at high altitudes, the effect of exercise has not yet been fully studied. Objective. To study the effect of short duration and casual exercise, on basal and post-prandial metabolic control in people with type 2 diabetes (DM2), residents at 3395 msnm. Methods. 14 women and 11 men with DM2, residents at high altitudes (Cusco, 3395 msnm), between 40 to 72 years old, who were intervened with two tests: baseline (A) and pre-postprandial exercise (B) consisting of a walk, for 30 minutes, at 4 Km/h (3 METS). Glucose, total cholesterol, HDL, triglycerides, insulin and non-esterified fatty acids (AGNE) were measured in the blood on fasting and after a breakfast with 730 Kcal (55,4% fat, 37,2% carbohydrates and 7,3% protein), for six hours. Additionally, total cholesterol, VLDL, LDL, NoHDL and HOMA-IR levels were calculated. Results. Statistically significant decrease (p<0,01) was found between the mean baseline (230,2 mg / dL) and post-prandial (115 mg / dL) glycemia. Conclusion. The exercise improved post-prandial glycemic control in DM2 in people who are living in high altitudes.